Peranan Penilaian Daur Hidup (Life Cycle Assessment) Dalam Menunjang Perolehan Program Penilaian Peringkat Kinerja Perusahaan (Proper) Pada Industri Mineral Timah - Lidia Handayani; Evelyn Hanaseta (Media Ilmiah Teknik Lingkungan (MITL), 2022)
The Ministry of Environment and Forestry added a new criteria, Life Cycle Assessment (LCA) on PROPER assessment 2021. This assessment aims to identify, calculate the sustainable usage of natural resources, discharge of pollution to environment as well as evaluate and implement possible environmental improvements. In the tin mining industry that has negative impact on the environment due to their activities, has to conducted life cycle assessment to support the acquisition of green PROPER. Asociation exporter tin Indonesia proposes scope of LCA from cradle to gate, this scope divided into an upstream process & tin smelterwhich consists of several processing units, namely preparing, smelting, refining, water treatment etc. Functional units are set as input and output references and have been normalized per 1 tonne of tin with impact categories as follows: Global warming, Ozone depletion, acidification potential, eutrophication, photochemical oxidant, abiotic depletion, human toxicity, land use, water footprint and carcinogenic